1996
DOI: 10.1038/ng0396-333
|View full text |Cite
|
Sign up to set email alerts
|

The complete BRCA2 gene and mutations in chromosome 13q-linked kindreds

Abstract: Breast carcinoma is the most common malignancy among women in developed countries. Because family history remains the strongest single predictor of breast cancer risk, attention has focused on the role of highly penetrant, dominantly inherited genes in cancer-prone kindreds (1). BRCA1 was localized to chromosome 17 through analysis of a set of high-risk kindreds (2), and then identified four years later by a positional cloning strategy (3). BRCA2 was mapped to chromosomal 13q at about the same time (4). Just f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
390
0
10

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 737 publications
(407 citation statements)
references
References 14 publications
3
390
0
10
Order By: Relevance
“…Germline mutations in the breast-cancer susceptibility gene BRCA2 confer susceptibility to familial early-onset breast and ovarian cancers (Wooster et al, 1994(Wooster et al, , 1995Tavtigian et al, 1996;Brody and Biesecker, 1998;Rahman and Stratton, 1998). Extensive studies have indicated that BRCA2 has an important function in DNA repair (Connor et al, 1997;Mizuta et al, 1997;Sharan et al, 1997;Wong et al, 1997;Chen et al, 1998;Patel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Germline mutations in the breast-cancer susceptibility gene BRCA2 confer susceptibility to familial early-onset breast and ovarian cancers (Wooster et al, 1994(Wooster et al, , 1995Tavtigian et al, 1996;Brody and Biesecker, 1998;Rahman and Stratton, 1998). Extensive studies have indicated that BRCA2 has an important function in DNA repair (Connor et al, 1997;Mizuta et al, 1997;Sharan et al, 1997;Wong et al, 1997;Chen et al, 1998;Patel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, five to ten percent of all breast and ovarian cancers are due to genetic predisposition with autosomal dominant transmission (Newman et al, 1988;Claus et al, 1991;Schildkraut et al, 1989). Two major breast and ovarian cancer susceptibility genes, BRCA1 (MIM# 113705) and BRCA2 (MIM# 600185), have been identified (Miki et al, 1994;Wooster et al, 1995;Tavtigian et al, 1996). These genes are believed to be tumor suppressors whose function has not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A series of genes has been identi®ed linking breast cancer with inherited mutations (BRCA1, BRCA2) (Miki et al, 1994;Tavtigian et al, 1996) as well as acquired mutations or gene ampli®cations in a series of oncogenes including HER-2 (Szollosi et al, 1995), ras (Miyakis et al, 1998), and myc (Visscher et al, 1997). These oncogenes encode proteins that induce signals leading to cell transformation and proliferation.…”
Section: Introductionmentioning
confidence: 99%